The Manual of Accounts and budgetary Control for the Rubber Industry (Book). - Bennett, George E. (The Accounting Review, 1927)
Reviews the book "The Manual of Accounts and Budgetary Control for the Rubber Industry," by The Accounting Committee of the Rubber Association of America.